Environmental water chemistry and possible correlation with Kaschin-Beck Disease (KBD) in northwestern Sichuan, China. (February 2017) - Shi, Zeming; Pan, Pujing; Feng, Yanwei; Kan, Zezhong; Li, Zhonghui; Wei, Fei
Abstract: During the past several decades, etiological and geochemical studies tend to link the Kaschin-Beck Disease (KBD) to the deficiency of some specific trace elements (e.g., selenium and iodine) in the environment; however the link has been proven inconclusive. In this work, we have investigated the relationship between KBD and the environment in a broader scope by examining comprehensively the chemistry of the surface waters in northwestern Sichuan, China, in relation to the KBD prevalence. The surface waters in the study area were found to be near neutral to slightly alkaline (pH 6.70 to 8.85 with a mean of 7.91) and mostly soft (total hardness 35.2 to 314.3 mg/L, mean 118.8 mg/L) with low salinity (total dissolved solids (TDS) 44.5 mg/L to 376.6 mg/L, mean 146.6 mg/L). The waters were dominated by cations Ca 2 + and Mg 2 + and anion HCO3 − ; whereas the alkali metal ions K + and Na + and the anions Cl − and S04 2 − were relatively scarce. Spatially, the hardness/salinity of the surface waters exhibited a characteristic of being lower towards the center of the study area where most severe KBD endemic has been observed. Even though it is not conclusive at this stage, a correlation between KBD prevalence and the salinity/hardness of the surface waters of an area has been demonstrated. As a postulate, the long-term consumption of such low salinity waters may lead to a deficiency of some essential elements such as Ca, Mg, Se and I in humans, which may be a factor in inducing KBD. However, other factors such as high altitude and cold climate, poor nutrition and sanitary conditions may play an important role in the disease endemic. Highlights: Relationship between KBD and the environment was studies by examining the chemistry of the surface waters in NW Sichuan, China; Surface waters in the study area were found to be near neutral to slightly alkaline, mostly soft and low in salinity; Spatially, water hardness/salinity was found to be lower towards the center of the area where most severe KBD has been observed; Long-term consumption of such soft and low salinity waters may lead to a deficiency of some essential elements in humans; And such a deficiency of essential elements such as Ca, Mg, Se and I in humans may be a factor in inducing KBD.